The Development of Contemporary Fatwas on Artificial Intelligence: A Comparative Study of Islamic Legal Reasoning - Mu'tasim Fikri; Ihsan Ihsan; Fiqi Restu Subekti; Renol Hasan; Fu'ad Sholikhi (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The rapid advancement of artificial intelligence (AI) has generated significant debates regarding its role in Islamic legal reasoning and the legitimacy of AI-assisted fatwas. This study aims to comparatively analyze the development of contemporary fatwas on artificial intelligence by examining the legal reasoning, epistemological foundations, and ethical principles adopted by contemporary Islamic scholars. A qualitative non-empirical approach was employed through a systematic literature review of recent academic publications and contemporary studies on AI, Islamic jurisprudence, fatwa authority, and digital governance. The findings identify three dominant jurisprudential models: restrictive, collaborative, and adaptive. Although these models differ in their evaluation of AI participation in legal reasoning, they consistently affirm that AI cannot independently perform ijtihad or replace qualified jurists. The analysis further demonstrates that contemporary debates have shifted from technological capability toward governance, accountability, and human oversight as the primary determinants of legal legitimacy. This study proposes an integrated governance framework that combines uṣūl al-fiqh, maqāṣid al-sharīʿah, and human-centered supervision to support the responsible integration of AI into Islamic legal institutions while preserving the epistemological integrity and normative authority of Islamic jurisprudence.